Invasive breast carcinoma with MRI kinetic curve type 1 - Christa Levina Daniswara; Rumuat Semuel Wullul Manangka (Indoscholar, 2020)
Breast cancer is the most common cancer in women and is the most significant cause of morbidity and mortality in women cancer patients. Increased awareness of people followed by periodic screening, appropriate supporting examinations, and imaging modalities according to the patient's condition could improve prognosis. We report a case report of a 55-year-old woman with a complaint of a lump in the right breast. Ultrasound examination and mammography showed a single solid lesion in the superior quadrant of the right breast corresponding to Breast Imaging-Reporting and Data System (BI-RADS) 4c. Magnetic Resonance Imaging (MRI) examination revealed a single lesion with enhancement curve type 1 according to bi-rads 4b. Results of the biopsy were grade 2 breast carcinoma without any lymph node metastases. The use of a single modality cannot be used as a benchmark in determining the best diagnosis and therapy. The kinetic feature/enhancement curve of Dynamic Contrast-Enhanced MRI (DCE-MRI) cannot be used as the main guide for determining the diagnosis. The morphology of the lesion either from ultrasound, mammography, or MRI should also be considered in determining the diagnosis and treatment plan.